Bioethanol and Beyond: A Comprehensive Review on Sustainable Biofuels for Global Energy Demands and Environmental Conservation - Kaushiky Sharma (Recent Trends in Infectious Diseases, 2023)
This comprehensive review explores the concept of "biofuels," specifically focusing on energy-enriched chemicals generated through biological processes or derived from the biomass of living organisms, including microalgae, plants, and bacteria. As the global population continues to increase, there is a growing demand for more energy supplies to enhance the quality of life. Biofuels, harnessed from various sources such as sugar, starch, and organic waste, have emerged as potential solutions to meet the escalating global energy demand. The paper emphasizes bioethanol, a renewable fuel produced through fermentation, as a significant biofuel that can be blended with gasoline to reduce vehicle emissions and reliance on foreign oil. Highlighting the importance of bioethanol in substituting petrol fuel for road transport vehicles, the paper discusses the top five countries in bioethanol production, emphasizing the need for alternative biomass sources to meet the rising demand. Additionally, the study delves into the environmental benefits of bioethanol, which produces lower emissions of carbon monoxide, nitrogen oxides, and CO2 compared to fossil fuels, contributing to efforts to mitigate global warming. The review concludes by addressing the sustainability challenges posed by the fermentation of economically important cultivars and underscores the potential of plant leftovers and agro-energy crops as low-cost, long-term biomaterials for biofuel production, offering a promising avenue for sustainable energy resources and addressing environmental concerns associated with fossil fuel combustion.
Keywords: Bioethanol; Biofuels; Fermentation; biomass; environmental issues